1996
DOI: 10.1093/clinchem/42.11.1765
|View full text |Cite
|
Sign up to set email alerts
|

Competitive RT-PCR to quantify CFTR mRNA in human endometrium

Abstract: Because the down-regulation by progesterone of cystic fibrosis transmembrane conductance regulator (CFTR) expression could be a useful specific marker to define the state of implant receptivity in endometrium, a competitive reverse transcription-polymerase chain reaction (RT-PCR) was developed for quantifying the CFTR mRNA concentration in human endometrial samples. A competitor RNA was constructed with the same sequence as the CFTR sequence except for a 20-nucleotide insertion in the middle. The amplified pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

1997
1997
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…In this method, the calibrator and target were amplified with different primers. Furthermore, some of the studies used an exogenous target-like IS RNA or DNA using dilutions of the IS for the quantification of the target mRNA (1,23,27,41). More recently, the quantification of the target mRNA has been carried out using a constant amount of IS in each sample and an external calibration curve consisting of the dilutions of calibrator and a constant amount of IS in each (2,28,38,39,42,44).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this method, the calibrator and target were amplified with different primers. Furthermore, some of the studies used an exogenous target-like IS RNA or DNA using dilutions of the IS for the quantification of the target mRNA (1,23,27,41). More recently, the quantification of the target mRNA has been carried out using a constant amount of IS in each sample and an external calibration curve consisting of the dilutions of calibrator and a constant amount of IS in each (2,28,38,39,42,44).…”
Section: Discussionmentioning
confidence: 99%
“…Table 2 summarizes some studies (2,23,27,28,38,39,42,44) that report the precision or the detection range of their QRT-PCR assays and that utilize an exogenous IS (panel A) and/or an external calibration curve (panel B). There are many RT-PCR assays each utilizing its own principle, which makes the direct comparison of different assays quite difficult.…”
Section: Discussionmentioning
confidence: 99%
“…CTFR is expressed in the endometrial epithelium of guinea-pigs and other animals. In human endometrium, CFTR is also widely expressed, and its expression changes in a cyclic manner [43,51]. In cultured glandular cells, it was found to be upregulated by progesterone and downregulated by estradiol [51][52][53].…”
Section: Cystic Fibrosis Transmembrane Conductance Regulator (Cftr) Amentioning
confidence: 99%
“…In human endometrium, CFTR is also widely expressed, and its expression changes in a cyclic manner [43,51]. In cultured glandular cells, it was found to be upregulated by progesterone and downregulated by estradiol [51][52][53]. The expression and role of CFTR in endometriosis has been evaluated by Huang et al [45]: in ectopic, endometrial-like samples, quantitative real-time polymerase chain reaction (qPCR) results demonstrated a significantly higher expression of CFTR mRNA and proteins in endometriotic lesions compared to normal endometria.…”
Section: Cystic Fibrosis Transmembrane Conductance Regulator (Cftr) Amentioning
confidence: 99%
“…Mutations of CFTR result in cystic fibrosis (CF), a lethal genetic disease with multi-organ defects, including infertility [ 18 , 19 ]. In the female reproductive tract, CFTR is expressed in the vagina, cervix, uterus, fallopian tube and ovary [ 20 22 ]. During the estrus cycle, the expression of CFTR in mouse endometrium is upregulated by estrogen [ 23 ] and downregulated by progesterone [ 24 ].…”
Section: Introductionmentioning
confidence: 99%